State regulation of economic activity of the countries of the world in the field of electricity: experience and prospects - Bilotserkivskyi, Oleksandr; Sosnov, Ihor (Global Scientific Trends, 2024)
The article is devoted to researching of the experience and prospectsof state regulation of economic activity of the countries of the world in the field of electricity. The authors show that the leading state body responsible for the processes of development and coordination of foreign economic activity in the field of electric power in the countries of the European Union at the current stage is the General Directorate for Energy. In most countries of the European Union, the functions ofelectricity transmission and management of power system regimes are organizationally united and implemented through system operators, which are currently united within the European network of transmission system operators for electricity (ENTSO-E), which performs the functions of planning and coordinating the functioning of energy systems operating in parallel, at the pan-European level. The authors conclude that in Europe and America, the “Single Buyer” model and the model “Liberalized “Single Buyer” are used. In China, the electricity market functions according to the “Single Buyer” model. In India, at the current stage, the “Model of Regulated Access to Power Transmission Networks” is used. In Brazil and South Korea, the presence of the electricity pool model is observed. The authors note that, according to forecasts of the International Energy Agency, by 2035, slightly more than 30% of the world's electricity will be produced from renewable energy sources. EU countries are recognized as the main leaders in the development of renewable energy sources.
Keywords: state regulation; economic activity; “Single Buyer” model; electricity pool mode; Energy Transition Index; renewable energy sources